2013
DOI: 10.1016/j.ahj.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in percutaneous coronary intervention outcomes among older patients in the United States

Abstract: Background New percutaneous coronary intervention (PCI) device technologies are often rapidly adopted into clinical practice, yet few studies have examined the overall impact of these new technologies on patient outcomes in community practice. Methods In hopes of determining temporal trends in PCI outcomes, we used data from the Centers for Medicare & Medicaid Service's Chronic Condition Warehouse (n = 3,250,836) by comparing patient characteristics and rates of 3-year major adverse cardiac events (MACE) acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Rao et al examined a temporal trend in the clinical outcome after PCI from 1991 to 2006 in a large cohort of Medicare beneficiaries. 12 In that study, a significant decrease in long-term clinical outcomes including death, MI and repeat revascularization was found. Patient background was unfavorable in the recent era of that study period, which was observed in the present study as well.…”
Section: Discussionmentioning
confidence: 91%
“…Rao et al examined a temporal trend in the clinical outcome after PCI from 1991 to 2006 in a large cohort of Medicare beneficiaries. 12 In that study, a significant decrease in long-term clinical outcomes including death, MI and repeat revascularization was found. Patient background was unfavorable in the recent era of that study period, which was observed in the present study as well.…”
Section: Discussionmentioning
confidence: 91%
“…The early, continuous and full opening of infarct-associated vessels to recover blood perfusion in the ischemic myocardium is the most important principle of treatment for AMI. In recent years, with the wide application of intravenous thrombolysis, percutaneous coronary interventions (PCI), coronary artery bypass grafting and other strategies, there has been an evident improvement in the symptoms and prognosis for patients with coronary heart disease and AMI (3). However, despite the numerous strategies available, it is common that clinical symptoms do not improve as expected.…”
Section: Introductionmentioning
confidence: 98%
“…The experiment was started when the myocardial cells grew close to conf luence, exhibiting synchronous growth cycles. Ischemia simulation solution components included NaH 2 PO 4 0.9 m mol/l, NaHCO 3 Trial grouping. The present study was divided into five groups according to an experimental scheme.…”
Section: Methodsmentioning
confidence: 99%
“…48 This has resulted in steady improvements in procedural and longerterm efficacy and safety across the spectrum of clinical presentation and risk. 52 In particular, two developments have revolutionized PCI: the introduction of DES and DAPT.…”
Section: ϯϯmentioning
confidence: 99%